Assessing the quality of support and discovering sources of resilience during COVID-19 measures in people with intellectual disabilities by professional carers. (April 2021) - Scheffers, Femke; Moonen, Xavier; van Vugt, Eveline
Highlights: During COVID-19 measures professional caregivers used more diverse and distal methods to maintain contact with people with ID. Professionals reported that the quality of the contact with people with ID had significantly decreased during COVID-19 measures. People with ID seem to have access to multiple sources of resilience during COVID-19 measures. Professionals can support people with ID in recognizing their own sources of resilience. Abstract: Background: During COVID-19 measures face-to-face contact is limited and professional carers have to find other ways to support people with intellectual disabilities. COVID-19 measures can increase stress in people with intellectual disabilities, although some people may adapt to or grow from these uncertain situations. Resilience is the process of effectively negotiating, adapting to, or managing significant sources of stress and trauma. The current study aims to provide professional carers with new insights into how they can support people with intellectual disabilities. Method: An online survey was shared through the social media and organizational newsletters of MEE ZHN (a non-governmental organization for people with disabilities). The resilience framework by Ungar (2019) was adapted to fit to people with intellectual disabilities during COVID-19 measures. Statistical analyses were performed in SPSS statistics version 26. Results: Results show that professional carers applied diverse and distal methods to maintain contact with people with intellectual disabilities during the COVID-19 measures. Professional carers reported a significant decrease in the quality of contact with clients with intellectual disabilities, but overall high levels of resilience in the same clients. Implications: Online methods of communication are possibly insufficient for professionals to cover all needs of people with intellectual disabilities. During this pandemic professionals should be aware of stress but also of resilience in people with intellectual disabilities.